1966
DOI: 10.1007/bf01645086
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical groups and spherical potentials in Classical Mechanics

Abstract: The one particle problem in a spherical potential is examined in Classical Mechanics from a group theorical point of view. The constants of motion are classified according to their behaviour under the rotation group $0(3), i.e. according to the irreducible representations D 0 of 80(3) (section 1).The Lie algebras of SO(4) and 80(3) are explicitly built in terms of Poisson brackets for an arbitrary potential, from global considerations. The Kepler and the 3 dimensional oscillator problems are shown to play part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

1973
1973
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 9 publications
0
45
0
1
Order By: Relevance
“…The algebraic relations of their conserved quantities reveal the dynamical symmetries of the two systems are described by the symmetry groups SO(3) and SU (2) respectively. This algebraic structure is called Higgs Algebra, and has received attention from a variety of literatures [14,15,16,17,18,19,20]. The Bertrand's theorem has been extended in different directions [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The algebraic relations of their conserved quantities reveal the dynamical symmetries of the two systems are described by the symmetry groups SO(3) and SU (2) respectively. This algebraic structure is called Higgs Algebra, and has received attention from a variety of literatures [14,15,16,17,18,19,20]. The Bertrand's theorem has been extended in different directions [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Bacry, Ruegg, Souriau [12] and Fradkin [13] made an important additional step when they showed that all three dimensional dynamical problems involving central potentials possess the extended symmetry algebra O 4 and SU 3 , a result subsequently generalized by Mukunda [14] for any Hamiltonian system with n degrees of freedom. As noted by Bacry, Ruegg and Souriau in their seminal paper [12], the general ability to construct such a local Lie algebra of dynamical symmetry is not surprising since all the 2n-dimensional symplectic manifolds are locally isomorphic [15].…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Bacry, Ruegg and Souriau in their seminal paper [12], the general ability to construct such a local Lie algebra of dynamical symmetry is not surprising since all the 2n-dimensional symplectic manifolds are locally isomorphic [15]. However the subsequent step to ensure a global dynamical symmetry is to verify that the finite canonical transformations generated by this algebra form a group, a feature of the Kepler problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are hundreds of papers [1][2][3][4][5][6][7][8][9][10] on the power, applications, and extensions of the Laplace-Runge-Lenz vector. The paper by Mukunda 11 comes closest to what we discuss below, but our aim is primarily pedagogical.…”
Section: The Kepler Problemmentioning
confidence: 99%